Novel gratings for next-generation instruments of astronomical observations - Ebizuka, N; Okamoto, T; Takeda, M; Hosobata, T; Yamagata, Y; Sasaki, M; Uomoto, M; Shimatsu, T; Sato, S; Hashimoto, N; Tanaka, I; Hattori, T; et al. (SPIE, 2017)
We will introduce current status of development of a birefringence volume phase holographic (B-VPH) grating, volume binary (VB) grating and reflector facet transmission (RFT) grating developing as the novel dispersive optical element for astronomical instruments for the 8.2m Subaru Telescope, for next generation 30 m class huge ground-based telescopes and for next generation large space-bone telescopes. We will also introduce a hybrid grism developed for MOIRCS (Multi-Object InfraRed Camera and Spectrograph) of the Subaru Telescope and a quasi-Bragg (QB) immersion grating. Test fabrication of B-VPH gratings with a liquid crystal (LC) of UV curable and normal LCs or a resin of visible light curable are performed. We successfully fabricated VB gratings of silicon as a mold with ridges of a high aspect ratio by means of the cycle etching process, oxidation and removal of silicon oxide. The RFT grating which is a surface-relief (SR) transmission grating with sawtooth shaped ridges of an acute vertex angle. The hybrid grism, as a prototype of the RFT grating, combines a high-index prism and SR transmission grating with sawtooth shape ridges of an acute vertex angle. The mold of the SR grating for the hybrid grism on to a work of Ni-P alloy of non-electrolysic plating successfully fabricated by using our ultra-precision machine and a single-crystal diamond bite. The QB immersion grating was fabricated by a combination of an inclined QB grating, Littrow prism and surface reflection mirror.